2020
DOI: 10.1111/ctr.13866
|View full text |Cite
|
Sign up to set email alerts
|

Clinical “real‐world” experience with letermovir for prevention of cytomegalovirus infection in allogeneic hematopoietic cell transplant recipients

Abstract: BackgroundLetermovir was approved in 2017 for prevention of cytomegalovirus (CMV) infection in seropositive (R+) allogeneic hematopoietic cell transplantation (HCT) patients. Post‐marketing data with this new agent are scarce.MethodsWe compared the incidence of both CMV reactivation (any viremia) and clinically significant CMV infection (CS‐CMVi; CMV DNAemia leading to preemptive treatment or presence of CMV tissue invasive disease) at days +100 and +200 post‐HCT in 25 adult allogeneic HCT patients who receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…Anderson and colleagues conducted a retrospective analysis of 25 patients who received letermovir and 106 patients who did not that assessed the use of letermovir outside of a clinical trial setting. They reported that the cumulative incidence of CS-CMVi at 100 days post-allo-HCT was only 4% in patients who received letermovir compared to 59% who did not receive letermovir [ 14 ]. Studer and colleagues also published a retrospective analysis similar to Anderson and colleagues, but with a larger patient population of 432 patients [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Anderson and colleagues conducted a retrospective analysis of 25 patients who received letermovir and 106 patients who did not that assessed the use of letermovir outside of a clinical trial setting. They reported that the cumulative incidence of CS-CMVi at 100 days post-allo-HCT was only 4% in patients who received letermovir compared to 59% who did not receive letermovir [ 14 ]. Studer and colleagues also published a retrospective analysis similar to Anderson and colleagues, but with a larger patient population of 432 patients [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Letermovir is an oral antiviral agent that inhibits the CMV-terminase complex to prevent CMV replication. Letermovir’s novel mechanism has no cross-resistance with other antiviral agents and has a favorable side effect profile, which makes it ideal for use in the prophylactic setting [ 13 , 14 ]. In controlled and retrospective trials, letermovir prophylaxis has demonstrated reduction in the incidence of CMV infection [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cases where a suitable CMV-matched donor cannot be identified, Letermovir offers a prohylactic treatment to reduce the risk of CMV reactivation for seropositive patients receiving a seronegative donation. As knowledge of the impact of letermovir in HPCT increases and more randomized clinical trials are conducted, its best use in CMV management will be further realized (Anderson et al, 2020;El Helou & Razonable, 2019).…”
Section: Society Of Blood and Marrow Transplantation And The Uk Virologymentioning
confidence: 99%